2009
DOI: 10.5194/angeo-27-461-2009
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of mesospheric gravity waves near the magnetic equator, Brazil, during the SpreadFEx campaign

Abstract: Abstract. As part of the SpreadFEx campaign, coordinated optical and radio measurements were made from Brazil to investigate the occurrence and properties of equatorial Spread F, and to characterize the regional mesospheric gravity wave field. All-sky image measurements were made from two sites: Brasilia and Cariri located ∼10 • S of the magnetic equator and separated by ∼1500 km. In particular, the observations from Brasilia provided key data in relatively close proximity to expected convective sources of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 74 publications
(100 citation statements)
references
References 57 publications
4
94
2
Order By: Relevance
“…Other assessments of gravity wave parameters have been made by Taylor et al (2009) during SpreadFEx, while Vadas et al (2009) have performed calculations of momentum fluxes, amplitudes and wave parameters for monochromatic GW events during the campaign. Their method was based in estimate GW properties of individual and prominent wave events present in the airglow images.…”
Section: Discussionmentioning
confidence: 99%
“…Other assessments of gravity wave parameters have been made by Taylor et al (2009) during SpreadFEx, while Vadas et al (2009) have performed calculations of momentum fluxes, amplitudes and wave parameters for monochromatic GW events during the campaign. Their method was based in estimate GW properties of individual and prominent wave events present in the airglow images.…”
Section: Discussionmentioning
confidence: 99%
“…16 were used in Vadas et al (2009a) to compare theoretical estimates with the observed amplitudes of the six medium-scale waves observed by Taylor et al (2008) in the OH layer, in order to constrain this theory. We first converted the measured intensity amplitudes to horizontal velocity amplitudes.…”
Section: Spectral Amplitudes At Airglow Altitudesmentioning
confidence: 99%
“…Among several techniques, radio frequency and optical measurements, airglow observations using a photometer and all-sky imagers have been effectively used. (Hecht et al, 1987;Taylor et al, 1991Taylor et al, , 2009Takahashi et al, 1992;Taori and Taylor, 2006). Airglow OH and O 2 emissions provide useful information on the variation of the hydrogen-oxygen chemistry and the temperature field.…”
Section: Introductionmentioning
confidence: 99%